Locoregional Anesthesia Due to Tumescence in Bilateral Total Mastectomy of Goats - Guimaraes, Gisele Pereira; Freire, Kelly Regina Freitas; Teixeira, Beatriz Blanc; Montenegro, Egle Raoni de Brito; Spindola, Bruno Ferreira; Helayel, Michel Abdalla; Caldas, Saulo Andrade (Acta Scientiae Veterinariae, 2022)
Background: Mastitis is an inflammation of the mammary gland or udder, regardless of its origin, severity, or evolution. Bilateral total mastectomy is indicated in cases of chronic suppurative mastitis, gangrenous mastitis, udder neoplasm or hyperplasia. For mastectomy, the supine position is recommended and, as it is a long-term procedure, general anesthesia was chosen together with the tumescence technique with the objective of transanesthetic and postoperative analgesia. The present report aims to report the general anesthesia protocol used for 2 goats submitted to bilateral total mastectomy associated with a locoregional block by tumescence, a technique not described in the goat species. Cases: Two female goats, mixed breed, approximately 3 years old, were admitted to the Hospital Veterinário de Grandes Animais (HVGA) of the Universidade Federal Rural do Rio de Janeiro (UFRRJ), with a history of recurrent mastitis. There was an increase in udder volume and the presence of purulent secretion during milking. One of the animals had given birth about 20 days ago. Surgical treatment through bilateral total mastectomy was recommended for both animals, as they did not present a satisfactory response to antimicrobial therapy, excessive enlargement and functional loss of the mammary system. For the procedure, food fasting for 48 h and water fasting for 24 h was established. The anesthetic protocols used consisted of previous sedation with xylazine¹ [Xilazin® - 0.05 mg/kg, IM] anesthetic induction with ketamine² [Ketalex® - 10 mg/kg, IV] and midazolam³ [Dormire® - 0.1 mg/kg, IV]. Orotracheal intubation and connection to the anesthetic circuit were performed for maintenance through inhalation anesthesia with isoflurane4 (Forane®) and oxygen therapy. Then, in bottle of lactated ringer’s solution5 [Linhamax® - 500 mL], lidocaine 2%6 without vasoconstrictor [Lidovet® - 40 mL] and adrenaline7 [Adren® - 25 mg/mL, 0.5 mL] were added, 10 mL/kg of the solution were injected into the subcutaneous tissue of the region of the mammary chains utilizing a Klein cannula after local antisepsis. After the administration of the tumescent solution, it was observed that the area involved is presented with the formation of a gel and there is minimal bleeding, compared to the conventional technique. The animals were monitored for the degree of analgesia, recording vital signs every 15 min at the end of the surgery, dipyrone9 [D-500® - 25 mg/kg, IV], morphine7 [Sulfato de Morfina® - 0.1 mg/kg, SC], and meloxicam10 [Maxican® 0.5 mg/kg, IM, 3 consecutive days] for postoperative analgesia. Additionally, tetanus serum1 [Vencosat® - 50,000 IU, single dose] and of oxytetracycline¹ [Oxitetraciclina LA® - 10 mg/kg, IM, 5 applications on alternate days)]. In the following 24 h, no signs of pain were observed on palpation of the surgical wound in the animals, but goat 1 was apathetic and inappetent, with improvement in the clinical picture only 48 h after surgery. Discussion: The choice of the surgical procedure resulted in an improvement in the clinical conditions of the animals and the anesthetic protocol using inhalation anesthesia and locoregional block (tumescence) proved to be efficient to perform in goats, contributing to transanesthetic and postoperative analgesia, being easily applied to ruminants that need surgical interventions in the region of mammary chains. Keywords: ruminant, mastectomy, local anesthetic, locoregional block.